2011
DOI: 10.1002/nbm.1553
|View full text |Cite
|
Sign up to set email alerts
|

Challenges towards MR imaging of the peripheral inflammatory response in the subacute and chronic stages of transient focal ischemia

Abstract: Intravenous administration of iron oxide nanoparticles after experimental stroke has been shown to produce focal signal intensity changes in the ischemic boundary on MRI images. These changes have been attributed to the influx of iron-laden blood-borne macrophages, although it has been suggested that this effect might not always be completely specific to inflammatory cells. The aim of the present study was to investigate this phenomenon in a subacute time frame that is more relevant to the peripheral inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
2
14
1
Order By: Relevance
“…The ischemic lesion was induced in 15 rats by transient (60 minutes) occlusion of the right middle cerebral artery (MCA), using the modified intraluminal filament technique [15], [16] under 2% isoflurane anesthesia in 30/70% O 2 /N 2 O. The body core temperature was measured with a rectal temperature probe and maintained at 36.7±1°C using an automated heating blanket with temperature feedback (Medres, Cologne, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The ischemic lesion was induced in 15 rats by transient (60 minutes) occlusion of the right middle cerebral artery (MCA), using the modified intraluminal filament technique [15], [16] under 2% isoflurane anesthesia in 30/70% O 2 /N 2 O. The body core temperature was measured with a rectal temperature probe and maintained at 36.7±1°C using an automated heating blanket with temperature feedback (Medres, Cologne, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…In this case, the presence of MRI contrast and iron-positive macrophages would not derive from the infiltration of iron-loaded blood-borne monocytes. Third, contrast enhancement may also be caused by general blood pool effects induced by the prolonged presence of a long-circulating contrast agent, such as Sinerem/Combidex [14]. Last, in case of severe BBB damage, iron oxides may also directly leak into the brain parenchyma [51], where they may be engulfed by activated macrophages/microglia or diffuse into the cerebrospinal fluid (CSF).…”
Section: Cellular Mri Of Leukocytesmentioning
confidence: 99%
“…Macrophages (ED1) and focal iron deposition were detected in the lesion at these timepoints, in agreement with T2/T2* hypointense areas. However, these results obtained with SPIO injection failed to be reproduced with USPIO in a recent study : Farr and colleagues did not observed T1,T2, nor T2* signal changes, despite a three-dose assay and extensive ED-1-positive macrophage accumulation at the sub-acute stage (Farr et al, 2011). In line with this negative results, the single study performed with a mouse model of transient ischemia reported no detectable MRI changes in the first 72h following stroke onset (Denes et al, 2007).…”
Section: Animal Modelmentioning
confidence: 91%